Pengaruh E-Leadership Kepala Sekolah terhadap Keinovatifan Guru di Madrasah Aliyah (Ma) Se-Kecamatan Pamijahan Kabupaten Bogor - Hana Lestari; Ima Rahmawati; Anika Firdaus; Muzhir Ihsan (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
The purpose of this study is to determine the influence of school principal e-leadership on the innovation of teachers in MA Se-Kecamatan Pamijahan Bogor. This research uses quantitative research. The data collected in the form of numbers were analyzed by linear regression analysis. This study used a questionnaire that was non-testing in nature. The questionnaire is systematically compiled by the researcher by submitting a written statement, answered by the respondent and returned to the researcher. The questionnaire in this study is a closed questionnaire, which is a questionnaire that contains the answers given by the researcher, until a respondent can only choose one answer that suits him. The questionnaire in this study contains a series of statements, including five alternative answers, and both positive and negative statements are answered by the teacher. Based on the regression test obtained a significant value of 0.000<0.05, it can be concluded that there is a positive and significant influence between the principal's e-leadership on teacher innovation. Keywords: E-Leadership; Inovation, Teacher